SLC2A1 is a Diagnostic Biomarker Involved in Immune Infiltration of Colorectal Cancer and Associated With m6A Modification and ceRNA - Liu, Xu-Sheng; Yang, Jian-Wei; Zeng, Jing; Chen, Xue-Qin; Gao, Yan; Kui, Xue-Yan; Liu, Xiao-Yu; Zhang, Yu; Zhang, Yao-Hua; Pei, Zhi-Jun (Frontiers in Cell and Developmental Biology, 2022)
Background: Overexpression of SLC2A1 promotes glycolysis and proliferation and migration of various tumors. However, there are few comprehensive studies on SLC2A1 in colorectal cancer (CRC). Methods: Oncomine, The Cancer Genome Atlas (TCGA), and Gene Expression Omnibus (GEO) databases were used to analyse the expression of SLC2A1 in pan-cancer and CRC and analysed the correlation between SLC2A1 expression and clinical characteristics of TCGA CRC samples. The expression level of SLC2A1 in CRC was certified by cell experiments and immunohistochemical staining analysis. The Genome ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA) analyses of SLC2A1 relative genes were completed by bioinformatics analysis. The correlation between SLC2A1 expression level and CRC immune infiltration cell was analysed by TIMER, GEPIA and TCGA database. The correlation between SLC2A1 expression level and ferroptosis and m6A modification of CRC was analysed by utilizing TCGA and GEO cohort. Finally, the possible competing endogenous RNA (ceRNA) networks involved in SLC2A1 in CRC are predicted and constructed through various databases. Results: SLC2A1 is highly expressed not only in CRC, but also in many other tumors. ROC curve indicated that SLC2A1 had high predictive accuracy for the outcomes of tumor. The SLC2A1 expression in CRC was closely correlated with tumor stage and PFS. GO, KEGG and GSEA analysis indicated that SLC2A1 relative genes were involved in multiple biological functions. The analysis of TIMER, GEPIA and TCGA database indicated that the SLC2A1 mRNA expression was mainly positively associated with neutrophils. By the analysis of the TCGA and GEO cohort, we identified that the expression of SLC2A1 is closely associated to an m6A modification relative gene (IGF2BP3) and a ferroptosis relative gene (GPX4). Conclusions: SLC2A1 can be used as a biomarker of CRC, which is associated to immune infiltration, m6A modification, ferroptosis and ceRNA regulatory network of CRC.